Chilled storage stability of spice marinated and high pressure processed Indian white prawns (Fenneropenaeus indicus). Issue 3 (3rd July 2021) - Joseph, Ginson; Kamalakanth, C. K.; Remya Kumari, K. R.; Bindu, J.; Asha, K. K.
ABSTRACT: Chilled storage stability of marinated and high pressure treated peeled and undeveined Indian white prawns ( Fenneropenaeus indicus ) were studied. The prawns were marinated with condiments viz. chilli powder, salt and turmeric, and - vacuum packed in ethylene-vinyl alcohol copolymer pouches. Marinated unpressurized prawn samples were kept as control. The products were stored at 2 ± 1°C for evaluating - shelf life by analysing biochemical, microbiological and organoleptic parameters. Pressurization significantly altered the quality indices such as pH, total volatile basic nitrogen, free fatty acid, thiobarbituric acid, total plate count and overall acceptability of samples. The control and 200 MPa treated sample were rejected on 20th and 25th day of storage respectively, whereas 250 and 300 MPa treated samples achieved a shelf life of 35 days. Among the samples, the prawns treated at 250 MPa were found to be organoleptically superior with respect to its biochemical and microbiological quality parameters.